Response of sesame (Sesamum indicum L.) to micronutrients and NPK levels on the growth, yield and nutrients uptake in coastal sandy soil: RESPONSE OF SESAME TO MICRONUTRIENTS AND NPK LEVELS IN COASTAL SANDY SOIL - D ELAYARAJA, (Journal of Oilseeds Research, 2015)
A pot experiment was conducted to find out the effect of NPK levels and micronutrients viz., Zn and Mn on the yield and nutrients uptake by sesame in coastal sandy soil. The experimental soil was sandy texture with pH 8.41, low in organic carbon, available N and P, medium in available K and deficient in Zn and Mn. The treatments consisted of different levels of NPK and micronutrients. The experiment was laid out in a factorial completely randomized design with three replications, using sesame variety TMV 7. The results of the study indicated that application of 150% NPK + ZnSO4 @ 25 kg/ha + MnSO4 @ 5 kg/ha recorded the highest seed and stalk yield of 52.4 and 184.7 g/pot, respectively. However, it was found to be on par with the treatment which received 125% NPK + ZnSO4 @ 25 kg/ha + MnSO4 @ 5 kg/ha and recorded the seed and stalk yield of 50.9 and 179.5 g/pot, respectively. Application of Zn and Mn along with NPK improved the uptake of micronutrients by sesame in addition to the yield and oil content.